Positioning the Quality Excellence Competitiveness of Integrated School Education Using the Multidimensional Scaling Model - Nugroho, Arif Julianto Sri; Haris, Abdul; Haryono, Purwo; Tasari, Tasari; Setyawanti, Dandang (Al-Hayat: Journal of Islamic Education, 2024)
This study was conducted by developing a performance analysis model of the competitiveness of Integrated Islamic Middle Schools (SMPIT). As a result of acquiring new students, SMPIT is experiencing increased student interest. The study aims to build a marketing strategy model based on competitive quality performance excellence and to determine the position of excellence of each SMPIT in Klaten City. The quantitative approach was used through a multivariate multidimensional scaling statistical test. The sampling technique used was purposive sampling, which included 112 respondents. The quantitative test of the model consists of the validity and reliability test of the instrument and the quantitative multidimensional scaling test of SMPIT competitiveness using the SPSS 21 program. This study produces attributes in the questionnaire including market orientation, program innovation, environmental adaptability and the influence of competitive advantage. The results of the quantitative test show that the instrument items are valid and reliable. SMPIT Ibnu Abbas and SMPIT Hidayah have the highest competitive advantage points in the competitiveness map of superior schools, both quantitative and qualitative, in Klaten Regency, namely in Quadrant I. The final stage of the research has formed a map of each SMPIT so that the competitiveness of superior Islamic high schools is created to welcome the era of demographic bonus and economic growth towards the golden generation of Indonesia in 2045. The novelty of this research is that it combines the concept of positioning the competitiveness of superior Islamic schools based on multidimensional scaling with the object of observation of secondary Islamic education. This study combines the idea of competitive advantage of the quality performance of Islamic educational institutions through the positioning of multidimensional scaling models.